Vogel and Motulsky's human genetics : problems and approaches - Speicher, Michael; Antonarakis, Stylianos; Motulsky, Arno G; Vogel, Friedrich (Springer, 2010)
The fourth, completely revised edition of this classic reference and textbook presents a cohesive and up-to-date exposition of the concepts, results, and problems underlying theory and practice in human and medical genetics. In the 10 years since the appearance of the third edition, many new data and insights have emerged for understanding the genetic and genomic basis of development and function in human health and disease. Human genetics, with its emphasis on molecular concepts and techniques, has become a key discipline in medicine and the biomedical sciences. While the chapters of this edition are written by multiple experts, the general spirit of this book highlighting problems, approaches, and history continues. The fourth edition has been extensively expanded by new chapters on timely topics such as epigenetics, pharmacogenetics, gene therapy, cloning, and genetic epidemiology, and databases for basic and clinical genetics. In addition, a multi-chapter section giving an overview on comparative genetics and the main model organisms useful for human genetics (mouse, dog, worm, fly, fish) has been introduced. This book is of interest to all human and medical geneticists, scientists in all biomedical sciences, physicians and epidemiologists, as well as to graduate and postgraduate students who desire to learn the fundamentals of this exciting and fascinating field.
Keywords: genetika, lékařská genetika; genetika člověka; Human Genetics